Large amplitude charge noise and random telegraph fluctuations in room-temperature graphene single-electron transistors - Fried, JP; Bian, X; Swett, JL; Kravchenko, II; Briggs, GAD; Mol, JA (Royal Society of Chemistry, 2019)
We analyze the noise in liquid-gated, room temperature, graphene quantum dots. These devices display extremely large noise amplitudes. The observed noise is explained in terms of a charge noise model by considering fluctuations in the applied source–drain and gate potentials. We show that the liquid environment and substrate have little effect on the observed noise and as such attribute the noise to charge trapping/detrapping at the disordered graphene edges. The trapping/detrapping of individual charges can be tuned by gating the device, which can result in stable two-level fluctuations in the measured current. These results have important implications for the use of electronic graphene nanodevices in single-molecule biosensing.